STRENGTHS AND WEAKNESSES OF SMART TOURISM DESTINATIONS: A CROSS-GENERATIONAL STUDY - Elena BOTEZAT; Olimpia BAN; Adela Laura POPA; Dorin Cristian COITA; Teodora Mihaela TARCZA; Lidia CHIRICOI (Annals of the University of Oradea: Economic Science)
Transforming tourism destinations using technology that makes the travel process efficient and pleasant for different generational groups is crucial. Any attempt to achieve this goal should start with an analysis of the feedback tourists provide about their digital experience at a destination. This study was carried out to gain an understanding of the perceptions of Romanian tourists of the strengths and weaknesses of smart tourism destinations as the first part of any SWOT analysis designed to collect critical factors about the current situation aiming to improve it to remain on a highly competitive market. The empirical data was obtained from 628 tourists belonging to Baby Boomers, Generation X, Generation Y, and Generation Z. The results showed, after a MAXQDA Analytics Pro analysis, that for all four generations considered, the number of respondents who identified strengths is higher than those who mentioned weaknesses. The study also found more similarities than differences across generations in tourists' perceptions of smart technology. Beyond Wi-Fi, destination marketers should focus on internet signal quality and mobile apps for improved travel experiences. However, generational gaps emerged: older generations valued ease of use, while younger ones prioritized access to information apps. Gen Y identified virtual experiences as a weakness, while Gen Z highlighted problematic applications By leveraging these tourism destination strengths, marketers can optimize their digital strategies, ensuring relevance and resonance across diverse demographic segments. Moreover, such insights empower tourism destinations to innovate more effectively, meeting the evolving needs and expectations of each generation in an increasingly digital landscape.